Residential contrustion Masonry - Meridian education Corporation (New Jersey : Shopware, 2004)
Basic skills in forming block wall foundations, different types of cement, and forming, pouring, and finishing concrete. Also includes skills in using mortar and bricklaying
Title from ttile screen
DVD format
Keywords: Building, Brick; Masonry; Dwellings -- Maintenance and repair